2018
DOI: 10.3892/or.2018.6207
|View full text |Cite
|
Sign up to set email alerts
|

Construction and investigation of lncRNA-associated ceRNA regulatory network in papillary thyroid cancer

Abstract: Increasing evidence has experimentally proved the competitive endogenous RNA (ceRNA) hypothesis that long non-coding RNA (lncRNA) can affect the expression of RNA targets by competitively combining microRNA (miRNA) via miRNA response elements. However, an extensive ceRNA network of thyroid carcinoma in a large cohort has not been evaluated. We analyzed the RNAseq and miRNAseq data of 348 cases of primary papillary thyroid cancer (PTC) patients with clinical information downloaded from The Cancer Genome Atlas (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 40 publications
3
79
0
Order By: Relevance
“…A number of recently conducted studies illustrated that abnormal lncRNA expressions are involved in the oncogenesis and development of various cancers, serving as tumor promoters or suppressors (32). A prior study reported that there exists a close link between LINC00284 and the overall survival of patients with papillary thyroid cancer (33). LINC00284 has been found to be highly expressed in human gastric cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recently conducted studies illustrated that abnormal lncRNA expressions are involved in the oncogenesis and development of various cancers, serving as tumor promoters or suppressors (32). A prior study reported that there exists a close link between LINC00284 and the overall survival of patients with papillary thyroid cancer (33). LINC00284 has been found to be highly expressed in human gastric cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…TCGA is the largest cancer genetic information database to study the genomic profiles of PTC. The ceRNA (lncRNA‐miRNA‐mRNA) network of PTC was once constructed based on the 348 PTC samples in TCGA . In this study, dysregulated RNAs were identified in three PTC variants, including classical PTC, follicular PTC, and tall‐cell PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed RNAs in 348 cases were identified in three PTC variants and were selected to construct the ceRNA network by Yanjing Zhao. 24 However, the ceRNA network of PTC is still poorly investigated in a larger cohort, and the validation analysis needs to be performed. In this study, dysregulated RNAs (including lncRNAs, miRNAs, and mRNAs) were detected in different stages and lymph node status, and these RNAs were used to construct the ceRNA network of PTC.…”
Section: Introductionmentioning
confidence: 99%
“…34 The genes with FDR value # 0.05 and |log 2 FC| $ 1 were considered the threshold of differential expression as reported earlier. 35…”
Section: Identication Of Differentially Expressed Genesmentioning
confidence: 99%